2013
DOI: 10.1371/journal.pone.0064393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MicroRNA Deep Sequencing of Matched Formalin-Fixed Paraffin-Embedded and Fresh Frozen Cancer Tissues

Abstract: MicroRNAs regulate several aspects of tumorigenesis and cancer progression. Most cancer tissues are archived formalin-fixed and paraffin-embedded (FFPE). While microRNAs are a more stable form of RNA thought to withstand FFPE-processing and degradation there is only limited evidence for the latter assumption. We examined whether microRNA profiling can be successfully conducted on FFPE cancer tissues using SOLiD ligation based sequencing. Tissue storage times (2–9 years) appeared to not affect the number of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 36 publications
(36 reference statements)
4
55
0
Order By: Relevance
“…Several studies have specifically addressed this issue and have shown that, although, RNA degradation is common, miRNAs are able to be accurately detected and quantified in FFPE tissue. 2426 Using the newer nCounter System from nanoString Technologies, we identified a profile of 41 significantly dysregulated miRs in cholangiocarcinoma relative to the adjacent normal bile duct epithelium. To date, an expression profile for microRNAs in cholangiocarcinoma has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have specifically addressed this issue and have shown that, although, RNA degradation is common, miRNAs are able to be accurately detected and quantified in FFPE tissue. 2426 Using the newer nCounter System from nanoString Technologies, we identified a profile of 41 significantly dysregulated miRs in cholangiocarcinoma relative to the adjacent normal bile duct epithelium. To date, an expression profile for microRNAs in cholangiocarcinoma has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The second unique feature of miRs is their length, which usually does not exceed 24 nucleotides; this makes them resistant to endonucleolytic cleavage. As such, miRs are relatively stable and can be detected and reliably measured in various biological materials, including archived formalin-fixed and paraffinembedded samples (3) or serum (4).…”
Section: Introduction On Micrornasmentioning
confidence: 99%
“…Given the evidence that miR profiles could potentially become predictive biomarkers for disease states, researchers are endeavoring to develop powerful bioinformatics approaches by analyzing routinely preserved samples such as formalin-fixed paraffin-embedded (FFPE) and laser-capture microdissected samples (50)(51)(52). Although mRNA is not stable in such sample preparations, miR has been demonstrated to be quite resilient.…”
Section: The Importance Of Sample Preparation and Rna Extractionmentioning
confidence: 99%